Analisis Penerapan Gotong Royong Sebagai Internalisasi Profil Pelajar Pancasila Dengan Model Berbasis Proyek - Apriyanti, Ade Irma; Awiria, Awiria (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to analyze the process of implementing project-based learning and the role of teachers in overcoming obstacles to fostering the value of mutual cooperation as one of the dimensions of the Pancasila Student Profile in class IV SDN Jayabakti 04. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the implementation of the value of mutual cooperation has been carried out through various project activities, such as cleaning and greening activities. Although there are challenges such as difficult coordination, and logistical obstacles, the PjBL model has been proven to increase students' awareness of the importance of cooperation and responsibility in group projects. Teachers play an important role as facilitators, motivators, and mentors in overcoming these obstacles. This study provides recommendations for optimizing project-based learning as an effort to strengthen the values ​​of mutual cooperation in students.